A Need Analysis in Learning English for Law Students - Herlina, Lina; Said, Mashadi (Advances in Social Sciences Research Journal, 2022)
The purpose of this study is to analyze the needs of law students in learning English and the value of language skills in English Specific Purposes (ESP), since we believe that ESP courses can assist students become more proficient in their field of study. This study was conducted at Nusa Putra University's Department of Law in Indonesia during the academic year 2020/2021. The participants in the study were given an ESP lesson once a week. The course lasted 14 weeks. Each meeting lasted 50 minutes. The survey included 40 male and female law students, as well as four departmental lecturers. Questionnaires and interviews were used to collect data. The findings revealed that the participants consider ESP classes to be extremely significant for their studies and future careers, and that they have a strong desire to take ESP courses and to improve their English language skills. Specific terminology is a barrier to efficient communication in English when it comes to the necessity of language skills in ESP. As a result, a greater emphasis on vocabulary development should be placed. After reviewing all of the study findings, we are certain that they can assist Law Department instructors in developing ESP curriculum that can be used by both learners and teachers. Keywords: Needs analysis; Law Department; ESP course; Language skills.